2022
DOI: 10.1021/acs.jafc.2c01784
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Digestive Fate and Antioxidant Activities of Polyphenols from Hulless Barley: Impact of Various Thermal Processing Methods and β-Glucan

Abstract: The unfavorable bioaccessibility of polyphenols in cereal-based food limits their physiological functions as most polyphenols bind spontaneously to the cell-wall polysaccharides. Effects of β-glucan and various thermal processing methods including flaking and roasting, stir-frying, steam-flash explosion, and popping expansion on the bioaccessibility and antioxidant properties of polyphenols from hulless barley in vitro and in vivo were investigated in this study. The bioaccessibility and antioxidant capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Superoxide radicals are relatively weak oxidants, but they can amplify cell damage by producing other kinds of free radicals and oxidants, such as hydrogen peroxide, hydroxyl radicals and singlet oxygen ( Xie et al, 2022 ). Superoxide anions can also indirectly initiate lipid peroxidation to form H 2 O 2 , the precursor of hydroxyl radicals was produced.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide radicals are relatively weak oxidants, but they can amplify cell damage by producing other kinds of free radicals and oxidants, such as hydrogen peroxide, hydroxyl radicals and singlet oxygen ( Xie et al, 2022 ). Superoxide anions can also indirectly initiate lipid peroxidation to form H 2 O 2 , the precursor of hydroxyl radicals was produced.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hydrolyzed amount far exceeded the continued dissolved amount, resulting in a decline in TPC after intestinal digestion. The increase in TPC in the exploded peels was much higher than in the unexploded peels after gastric digestion, suggesting that steam explosion contributed to disconnecting the interaction formed between phenols and other compounds ( 14 ). In addition, the four phenolic compounds in pomegranate peel were easily degraded or transformed during in vitro digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al used the steam explosion to extract flavonoids from fig leaves and found that the content of flavonoids from the treated samples was 55.9% higher than that in the control group ( 13 ). Xie et al suggested that steam explosion-treated hulless barley exhibited potent antidiabetic effects and antioxidant capacity ( 14 ). Wan et al reported that steam explosion enhanced the phenolic profiles and antioxidant activity in mung beans ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid was used as standard and for the calculation of the percentage of inhibition the following relation was used: %Inhibition = [Blank − Test]/Blank × 100. A second test to evaluate the antioxidant activity was carried out through the determination of total phenols by the ABTS and Folin–Ciocalteu technique, according to the methodology previously reported [ 28 , 29 , 30 , 31 ]. The same doses mentioned above were used for the test, and the results were reported as equivalents of gallic acid.…”
Section: Methodsmentioning
confidence: 99%